Pore constrictions in intervessel pit membranes provide a mechanistic explanation for xylem embolism resistance in angiosperms. Issue 5 (27th March 2021) - Kaack, Lucian; Weber, Matthias; Isasa, Emilie; Karimi, Zohreh; Li, Shan; Pereira, Luciano; Trabi, Christophe L.; Zhang, Ya; Schenk, H. Jochen; Schuldt, Bernhard; Schmidt, Volker; Jansen, Steven
Summary: Embolism spreading in angiosperm xylem occurs via mesoporous pit membranes between vessels. Here, we investigate how the size of pore constrictions in pit membranes is related to pit membrane thickness and embolism resistance. Pit membranes were modelled as multiple layers to investigate how pit membrane thickness and the number of intervessel pits per vessel determine pore constriction sizes, the probability of encountering large pores, and embolism resistance. These estimations were complemented by measurements of pit membrane thickness, embolism resistance, and number of intervessel pits per vessel in stem xylem ( n  = 31, 31 and 20 species, respectively). The modelled constriction sizes in pit membranes decreased with increasing membrane thickness, explaining the measured relationship between pit membrane thickness and embolism resistance. The number of pits per vessel affected constriction size and embolism resistance much less than pit membrane thickness. Moreover, a strong relationship between modelled and measured embolism resistance was observed. Pore constrictions provide a mechanistic explanation for why pit membrane thickness determines embolism resistance, which suggests that hydraulic safety can be uncoupled from hydraulic efficiency. Although embolism spreading remains puzzling and encompasses more than pore constriction sizes, angiosperms are unlikely to have leaky pit membranes, which enables tensile transport of water.